2020
DOI: 10.1136/bmjopen-2020-039449
|View full text |Cite
|
Sign up to set email alerts
|

PropAngio study protocol: a neoadjuvant trial on the efficacy of propranolol monotherapy in cutaneous angiosarcoma—a proof of principle study

Abstract: IntroductionAngiosarcoma is a rare and aggressive malignancy with a high metastatic potential and recurrence rate. Despite optimal treatment with surgery, with or without radiation, the prognosis remains poor and, therefore, new treatment strategies are warranted. Recently, propranolol has effectively been repurposed for the treatment of infantile haemangioma. Propranolol is a β3-sparing antagonist of the β-adrenergic receptor. In infantile haemangioma, the β1, β2 and β3 receptors are highly expressed. Angiosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…257 In fact, a current huge PropAngio clinical trial is recruiting participants with cAS to estimate effectiveness of propranolol as a neoadjuvant monotherapy. 258 The newest study showed that HSAs overexpress three β-AR subtypes: ADRB1, ADRB2 and ADRB3, 259 thus, β-AR antagonists could be used as adjunct drugs to current therapeutic strategies, especially to overcome DOX-resistance. 252 Repurposing of propranolol with weak base chemotherapeutics, such as DOX, in a canine cohort is supported by studies conducted by Saha et al 252 in which increased cytotoxicity and reduction of the drug resistance has been achieved without significant AEs.…”
Section: Propranololmentioning
confidence: 99%
“…257 In fact, a current huge PropAngio clinical trial is recruiting participants with cAS to estimate effectiveness of propranolol as a neoadjuvant monotherapy. 258 The newest study showed that HSAs overexpress three β-AR subtypes: ADRB1, ADRB2 and ADRB3, 259 thus, β-AR antagonists could be used as adjunct drugs to current therapeutic strategies, especially to overcome DOX-resistance. 252 Repurposing of propranolol with weak base chemotherapeutics, such as DOX, in a canine cohort is supported by studies conducted by Saha et al 252 in which increased cytotoxicity and reduction of the drug resistance has been achieved without significant AEs.…”
Section: Propranololmentioning
confidence: 99%
“…Two very similar phase 2 clinical trials, in the EU (EudraCT: 2019-002947-41) and in the USA (NCT04518124), developed by the Netherlands Cancer Institute, are active and ongoing during the writing of this review [68]. The clinical response to oral propranolol as monotherapy in patients with angiosarcoma will be evaluated as primary endpoint and histological response as secondary endpoint (Ki-67 as biomarker).…”
Section: Angiosarcomamentioning
confidence: 99%
“…Hence, propranolol obtained the orphan designation by the European Commission for the treatment of soft tissue sarcomas ( 6 , 7 ). Furthermore, the effect of β-receptor blockade with propranolol on angiosarcoma is currently being studied in two clinical trials: The PropAngio trial (NCT04518124, study start date December 2019, status ongoing) and the PROPAN trial (NCT02732678, study start date May 2016, status unknown) ( 8 – 10 ). The aim of the PropAngio trial is to prospectively assess the anti-proliferative effect of neoadjuvant propranolol as monotherapy in primary, recurrent and metastatic angiosarcoma.…”
Section: Introductionmentioning
confidence: 99%